(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The development of digital technology presents both opportunities and challenges for parents in assisting early childhood. A lack of understanding about the correct and safe use of digital media often exposes children to inappropriate content and lacks optimal guidance. This study aims to improve parents’ understanding of the function of digital parenting, how to provide guidance, and the wise use of digital media for early childhood. The research method used a descriptive qualitative approach. The research subjects consisted of parents of students at Pembina Pejagan State Kindergarten, selected through purposive sampling. Data collection techniques used in this study were observation, interviews, and documentation. The data analysis technique in this study used technical triangulation. The results of the study indicate that parents’ understanding of digital guidance has increased, based on participatory observation and input from participants. Parents increasingly understand the importance of limiting screen time, selecting educational applications, and active communication when children use digital devices. This activity shows that direct education through socialization and guidance successfully improves parents’ digital literacy. A practical workshop as a follow-up program is recommended so that parents’ skills can continue to develop and be consistently applied within the family environment